University Library as an object of evaluation - E. N. Opekunova (Библиосфера, 2013)
The problem of evaluating the activity of university libraries is studied. Different periods of library statistics development are considered. The conclusions on the necessity to review some of the evaluation criteria in connection with the recent changes in the field of library activity are made